2008
DOI: 10.1080/13645700701820242
|View full text |Cite
|
Sign up to set email alerts
|

Haptics in minimally invasive surgery – a review

Abstract: This article gives an overview of research performed in the field of haptic information feedback during minimally invasive surgery (MIS). Literature has been consulted from 1985 to present. The studies show that currently, haptic information feedback is rare, but promising, in MIS. Surgeons benefit from additional feedback about force information. When it comes to grasping forces and perceiving slip, little is known about the advantages additional haptic information can give to prevent tissue trauma during man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(151 citation statements)
references
References 63 publications
0
151
0
Order By: Relevance
“…Kinesthetic feedback distortion can be attributed to the following disturbance factors: trocar friction, abdominal wall resistance, scaling factors, mechanical construction, and efficiency [1]. Of the three instruments used in this experiment, tweezers caused the least kinesthetic distortion.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Kinesthetic feedback distortion can be attributed to the following disturbance factors: trocar friction, abdominal wall resistance, scaling factors, mechanical construction, and efficiency [1]. Of the three instruments used in this experiment, tweezers caused the least kinesthetic distortion.…”
Section: Discussionmentioning
confidence: 94%
“…Stiffness is important because it determines the magnitude of the force required by a surgeon for pulling and pinching to manipulate the tissue. Incorrect pinch force control causes tissue slippage, damage, or both [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these situations can lead to tissue trauma. Frequent study towards this matter has been carried out and reported [27]- [30]. Device development to represent grasp virtually [31] also rising up.…”
Section: The Graspmentioning
confidence: 99%
“…Even though many research has been carried out recently on laparoscopy surgery skill training [4], [5], [8], technologies and modeling of tissues [25]- [27] and also development made for laparoscopy skill training [12], [14]- [16], [18], [21], [24], [28]- [30] but most of the application developed or experiment carried out focuses on task but none of it provide for a single and complete surgery procedure such as hernia repair, cyst remove and etc. Research in grasp control shown that surgeons perform better if suitable application that provide force feedback thus help them in improve their skill ability [28]- [30].…”
Section: Literature Reviewmentioning
confidence: 99%